Leksikal Tanaman Obat Tradisional Untuk Penyakit Anak Dalam Lontar Usadha Rare - Sutrisna, I Putu Gede; Bhandesa, Asthadi Mahendra; Mahaputra, I Nyoman Arya; Harditya, Kadek Buja; Damayanti, Ida Ayu Manik (Jayapangus Press, 2024)
The lack of attention to medicinal plants will cause the ecosystem and lexical medicinal plants to become more critical. Therefore, an in-depth study is needed to save biodiversity and lexical preservation of medicinal plants. The objectives of this study are (1) to describe the lexical medicinal plants in lontar Usada Rare; (2) to describe the clarification of usada figures related to traditional medicinal plants in lontar Usada Rare for childhood diseases. To achieve these objectives, the researcher used a qualitative descriptive design. Data collection in the first stage was carried out by content analysis on lontar Usada Rare. The second stage of the research design was an in-depth interview with usada figures about usada rare to clarify the content of the lontar.The researcher as a human instrument is equipped and supported by interview guidelines, recording devices, cameras, and notes. The data obtained through the Usada Rare manuscript, then carried out data review, data categorization, and extracting the value and concept of treatment. The analysis techniques in this research are 1) data reduction, 2) data presentation and 3) conclusion drawing. Based on the results of the research and discussion above, the conclusions in this study are as follows. There are 111 (One hundred and eleven) lexical medicinal plants in lontar usada rare; There are 4 balian/healer terms in usada bali namely balian ketakson, balian kepican, balian usada and balian campuhan. The sources of medicine in usada bali include: Taru Pramana (Trees with medicinal properties), Sato Pramana (Medicinal ingredients derived from animals), Toya Pramana (Medicinal ingredients derived from water), Bayu Pramana (Medicinal ingredients derived from strength).